Proc je odpovĕd na kombinovanou lécbu interferonem alfa2b a ribavirinem u pacientů s chronickou hepatitidou C tak slabá? - Stránský, J; Rýzlová, M; Stríteský, J; Nĕmecek, V (Casopis lekaru ceskych, 2002)
BACKGROUND: Patients with chronic hepatitis C are now treated with a combination of interferon alpha (IFN) and ribavirin. Therapy was used in initial treatment, for those who were resistant to interferon and in relapsed patients. The aim of the study was to evaluate our results and to compare them with the already published data. METHODS AND RESULTS: 27 adult patients of the average age 46 years were cured from 1997 through 1999 for the histologically verified chronic hepatitis C with IFN-alpha 2 and ribavirin. 16 patients suffered from the chronic hepatitis with low, medium or high activity, 11 of them had cirrhosis. Serological testing was done using ELISA-3 test HCV RNA in serum was estimated by the polymerase chain reaction and serotype HCV was identified by the Murex kit. Treatment lasted 6 to 12 months. Incidences of side effects to both remedies, complications in therapy, therapeutical responses and possible failures of the combination therapy were analysed. In 20/27 patients the HCV serotype could be identified and always serotype 1 was found. Average score of histological activity was in patients with serious chronic active hepatitis and cirrhosis 10.1, in other patients 5.6. Sustained biochemical and virological response was found in 5 out of 27 patients (18.5%). Their average age was 39 years. 9 patients (33%) of average age 49 years had no biochemical and virological response. Sustained biochemical response without the accompanying virological response was found at the end of therapy in 10 patients (37%). After the end of therapy, 33% of patients had a relapse. The most frequently seen accompanying sign was the flu-like syndrome, in two female patients we found impairment of thyroid gland function, and in another two the breakthrough phenomenon. Treatment with ribavirin was in seven cases (26%) complicated with rather serious haemolytic anaemia and the dose had to be reduced. Toxic-allergic exanthema in 5 patients (18.5%) represented the second serious complication causing the termination of therapy. CONCLUSIONS: Sustained biochemical and virological response to the combination therapy was found only in patients with mild form of chronic hepatitis C. No such response was found in 8 patients with cirrhosis and in one female patients with medium activity of the chronic hepatitis. The age of patients with sustained response was significantly lower than in patients without the response (39 years versus 49 years). The most frequent serotype was HCV 1. The combination therapy was more frequently accompanied with clinically serious complications. To the adverse effects to the combination therapy belonged in our population the liver cirrhosis, age about 50 or more years, and the genotype HCV 1. It is also the answer to the question why the combination therapy of patients with chronic HCV infection has so poor results.
Keywords: recidiva; Humans; Interferon-alpha; lidé středního věku; Hepatitis C, Chronic; Female; Aged; dospělí; ribavirin; senioři; lidé; Recombinant Proteins; Adult; rekombinantní proteiny; ženské pohlaví; chronická hepatitida C; Male; Middle Aged; antivirové látky; Antiviral Agents; Recurrence; interferon alfa; interferon alfa-2; mužské pohlaví; kombinovaná farmakoterapie; Ribavirin; Drug Therapy, Combination; Interferon alpha-2